A Landslide of Images. A Story that is Not History 2014-2015 - Medina , Cuauhtémoc (Re-visiones, 2024)
Analysis of the way the protest movement triggered by the enforced disappearance and murder of students from Ayotzinapa was activated by the public impact of certain images and the creation of a public space of demonstration likewise constructed with images.